By-products of walnut (Juglans regia) as source of bioactive compounds for the formulation of nutraceuticals and functional foods - Chamorro Rivo, Franklin Noel (2022)
The scarcity of natural resources and a higher incidence of diseases related to inappropri-ate eating habits have focused research on the search for food and nutraceutical products with func-tional properties that are respectful of the environment. Agro-industrial by-products are a profitable source for obtaining bioactive compounds, with various biological properties, including antioxi-dant, anti-inflammatory, and anticancer properties, which contribute to immunity and reduce the negative effects of infections, inflammation, and oxidative stress. In the case of the walnut oil indus-try, various by-products are generated, among which we can mention pomace, green shell, shell, skin and leaves. Therefore, there is an opportunity for the recovery of waste, the recovery of target molecules and the formulation of new products, whether they are nutraceuticals, pharmaceuticals, or food additives, contributing to the circular economy and consumer health. The nut is commonly characterized by its high content of lipids (58–65%), mainly polyunsaturated fatty acids, tocopherols and phytosterols. In addition, the current literature states that its by-products are rich in phenolic compounds, mainly phenolic acids and flavonoids, for example total phenolic concentrations in the range 74 to 410 mg/g of GAE/FW are reported. In accordance, it is reported that the antioxidant potential of different extracts of nuts, shells and leaves was studied using different methods such as the reduction potency assay, scavenging effect of DPPH (2,2-diphenyl-1-picrylhydrazyl) and in-hibition of lipid oxidation by β-carotene linoleate system, with EC50 values less than 1 mg/mL. The results obtained showed that all walnut extracts have a strong antioxidant capacity against ROS species. For this reason, this work focuses on the bibliographic review of the bioactive compounds present in the by-products of the walnut (Juglans regia) industry, as well as mentioning their biolog-ical properties and possible applications in the food industry